Genetic Alterations in Patients with Two Clinical Phenotypes of Multiple Sclerosis - Feliciano, Luciana Maria [UNESP]; Sávio, André Luiz Ventura; de Castro Marcondes, João Paulo; da Silva, Glenda Nicioli; Salvadori, Daisy Maria Fávero [UNESP] (Springer Nature, 2020)
The etiology of multiple sclerosis (MS) is still not known, but the interaction of genetic, immunological, and environmental factors seem to be involved. This study aimed to investigate genetic alterations and the vitamin D status in patients with relapsing-remitting MS (RRMS) and secondary progressive MS (SPMS). A total of 53 patients (29 RRMS; 24 SPMS) and 25 healthy subjects were recruited to evaluate the micronucleated cell (MNC) frequency and nuclear abnormalities in the buccal mucosa, gene expression profiling in mononuclear cells, and plasmatic vitamin D concentration in the blood. Results showed a higher frequency of cells with karyorrhexis (SPMS) and lower frequencies of nuclear pyknosis (RRMS and SPMS) and karyolysis (SPMS) in patients with MS. Significant increase in the frequency of MNC was detected in the buccal mucosa of RRMS and SPMS patients. HIF1A, IL13, IL18, MYC, and TNF were differentially expressed in MS patients, and APP was overexpressed in cells of RRMS compared to SPMS patients. No relationship was observed between vitamin D level and the differentially expressed genes. In conclusion, the cytogenetic alterations in the buccal mucosa can be important indicators of genetic instability and degenerative processes in patients with MS. Furthermore, our data introduced novel biomarkers associated with the molecular pathogenesis of MS.
Keywords: Biomarkers; Buccal mucosa; Micronucleated cell; Multiple sclerosis; Vitamin D